(untitled) (Journal of Plant Disease Sciences, 2025)
Pea ( L.) is one of the most important legume crop after chickpea in Pisum sativum India. In the present investigation, keeping in view these facts, roving survey was conducted during 2018-19 and 2019-20 to obtain information on the natural disease incidence and distribution of Pea diseases in the farmers’ fields in four different districts of Madhya Pradesh. Apooled mean of seed and seedling disease ranging from 10.19 to 41.22%, wilt incidence ranging from 23.46 to 42.53 %, Powdery mildew incidence ranging from 41.29 to 59.62% and Downy mildew incidence ranging from 1.97 to 18.33% was observed during 2018-19 and 2019-20. Diseases transmitted through seeds are becoming a significant threat to the production of peas.(Katni, Mandla, Narsinghpur and Jabalpur).